2017
DOI: 10.3390/rs9090888
|View full text |Cite
|
Sign up to set email alerts
|

The 2015 Surge of Hispar Glacier in the Karakoram

Abstract: Abstract:The Karakoram mountain range is well known for its numerous surge-type glaciers of which several have recently surged or are still doing so. Analysis of multi-temporal satellite images and digital elevation models have revealed impressive details about the related changes (e.g., in glacier length, surface elevation and flow velocities) and considerably expanded the database of known surge-type glaciers. One glacier that has so far only been reported as impacted by surging tributaries, rather than surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 42 publications
(54 reference statements)
8
48
0
Order By: Relevance
“…Future field observations should focus on finding possible evidence for these processes and possible feedback processes, especially related to the deformation of water-saturated granular base material that could explain these extreme acceleration rates and peak velocities (Damsgaard et al, 2015). The surface velocities observed during the peak surge in May 2017 on Khurdopin Glacier are, together with the recently observed surge on the neighbouring Hispar Glacier (Paul et al, 2017), the fastest so far reported for the region. In their magnitude and rapid acceleration and deceleration they are comparable to similar bursts at the closely investigated Variegated Glacier (Kamb et al, 1985), where observations with even higher temporal resolution were available.…”
Section: Discussionmentioning
confidence: 99%
“…Future field observations should focus on finding possible evidence for these processes and possible feedback processes, especially related to the deformation of water-saturated granular base material that could explain these extreme acceleration rates and peak velocities (Damsgaard et al, 2015). The surface velocities observed during the peak surge in May 2017 on Khurdopin Glacier are, together with the recently observed surge on the neighbouring Hispar Glacier (Paul et al, 2017), the fastest so far reported for the region. In their magnitude and rapid acceleration and deceleration they are comparable to similar bursts at the closely investigated Variegated Glacier (Kamb et al, 1985), where observations with even higher temporal resolution were available.…”
Section: Discussionmentioning
confidence: 99%
“…Georeference errors are compensated by the estimation of a polynomial bias 25 surface through areas outside glaciers (i.e., assumed stable). The glacier mask used for that purpose is from the Randolph Glacier Inventory (RGI) (Pfeffer et al, 2014). The resulting grids come in Universal Transverse Mercator (UTM) projection and if orthorectification errors are minimal, displacements for precise georeferencing require only horizontal movement of a few meters (generally <10 m).…”
Section: Golive Velocity Fieldsmentioning
confidence: 99%
“…Up to now, most studies of glacial velocity have had an emphasis on either spatial or temporal detail. When temporal detail 20 is present, studies focus on a single or a handful of glaciers (Scherler et al, 2008;Quincey et al, 2011;Paul et al, 2017). On the other hand, when regional assessments are the focus, the temporal resolution ranges from a single time stamp up to annual resolution (Copland et al, 2009;Dehecq et al, 2015;Rosenau et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Glacier dynamics in the Central Karakoram have a significant influence on the hydrological cycle, especially hydrological planning and water resource management. As one of the crucial factors in mass balance and glacier dynamics [14], the glacier surface velocity provides an indicator of glacier recession or advance/surge [15][16][17] and has been used to interpret glacier dynamics [18]. Therefore, the spatial-temporal characteristics of the glacier velocity in this region are essential to improve our understanding of glacier dynamics and the glacier responses to climate change and influences on regional water sources.…”
Section: Introductionmentioning
confidence: 99%